Professional identity in relation to vocational teachers' work: an identity-centred approach to professional development. (2nd January 2019) - Vähäsantanen, Katja; Hämäläinen, Raija
ABSTRACT: This paper reports a study on teachers' professional identity and work in vocational education. The findings showed that vocational teachers' work included vocational teaching within the school, developmental work, technology-enhanced work, professional duties outside the school, and educational duties within the school. Furthermore, the study revealed the harmonious and tensioned relationships between these elements of the work and teachers' identities. Recognition of the nuanced nature of these relationships provides a perspective for promoting teachers' professional development. From a practical perspective, there is a need to support vocational teachers' identity work and the adoption of new technologies for their teaching. The findings also illuminate the emotionally imbued relationship between work and professional identity.